Cardiac Patients for Non-Cardiac Surgery: Anesthetic Management in Patients with Permanent Pacemaker - Eva Oktavia; Eva Oktavia (Jurnal Kardiologi Indonesia, 2020)
Permanent pacemaker (PPM) are being used in greater frequency in managing patients with electrophysiology disorders. These patients can be presented for either cardiac or non-cardiac surgery after their device implantation. They also will undergo either general or regional anesthesia to facilitate the surgical procedure. As an anesthesiologist, understanding patients’ condition, pacemaker care and safe anesthetic technique of choice are very important to provide safe patient management. Therefore, this literature reviewed and summarized a systematic approach which can be followed in managing these patients. Various approach and guidelines have been discussed in the literature on how to manage patients with PPM who will undergo anesthesia. In this literature, the American Society of Anesthesiology (ASA) standard was used as a framework for managing patients with PPM. Meanwhile, the decision of anesthesia technique that being chosen should be based on patients’ clinical condition, the surgical procedure itself, the duration of surgery, and the convenience of the surgeon. Overall, patients with PPM require special attention in perioperative management. Both anticipations of the patient’s condition and the performance of PPM must always be considered to provide safe anesthesia practice.